DEVELOPING ICT-BASED READING MATERIALS FOR GRADE-EIGHT STUDENTS OF JUNIOR HIGH SCHOOL - I Nyoman, Arimbawa,; Nitiasih, Kerti; I Nyoman, Sudiana, (Jurnal Pendidikan Bahasa Inggris, 2013)
Abstract Â  This study was aimed at developing ICT-based reading materials for grade-eight students of Junior High School at SMPN 1 Kubutambahan which met the criteria of good reading materials and investigating whether the ICT-based reading materials were able to improve the studentsâ reading competency. It was conducted through seven steps: need analysis, product design, design evaluation, design revision, field test (CAR), product revision and prototype product. The data were collected using questionnaires and reading tests. The data obtained were analyzed qualitatively and quantitatively. Based on the findings of this study, it was concluded that (1) the ICT-based reading materials could be developed through need analysis, then designing the product, evaluating the product design by experts, revising the product design, field-testing the product (through CAR), re-revising the product and finally producing the prototype product; (2) the ICT-based reading materials were able to improve the studentsâ reading competency significantly. Â  Keywords: ICT, material development, and reading materials.